(3bWQ GdSjd aj SjGSI GdNjd hYdGeGJgG GdLjOI hGdQOjFI hajg TjF ef WHgG heG jhGabgG ef dCOhjIs - (3SQGL GdOjf YeQ Hf QSdGf GdHbjfis; (3GdHdbjfj , SQGL GdOjf,J (B805 (3g` s
(3ChdgG (B:s
(3hHYO abO bGd Gddg JYGdi ai eMce GdBjGJ (B((3hGdNjd hGdHZGd hGdMejQ dJQcHhgG hRjfI hjNdb eGdG JYdehf(B) s
(3BNQgG (B:s
(3hBPGfgG WhGd dG JbQHgG hdGJQcHgG hdGJbJfjgG CHOkG hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH hGdMeO ddg QH GdYGdejf s
(3CVGa Edjg CTjGA hLYdg SHYI aUhds
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B284s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B74 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B89 s
Keywords: (3GdcjejGA h GdWHjYjGJs